Determinants of Payment Method in Mergers and Acquisitions : A Study on Indian Companies - Bijay Sankar, B. P.; Leepsa, N. M. (Indian Journal of Finance, 2021)
The study empirically investigated the determinants that affected the decision-making of payment methods in mergers and acquisitions (M&As) in the Indian context. The sample for the study covered the M&A deals that acquirer companies announced from the non-financial sector. The binary logistic regression model was used to find out the determinants that affected the payment method of Indian M&As. Descriptive statistics and independent-sample t-test were used to know the behavior of the explanatory variables. It was found that there was a positive relation between acquirer cash availability, promoter shareholdings, unlisted targets, and targets from the unrelated industry with cash payment methods in Indian M&A deals. It was also documented that the determinants like the amount of deal value and acquirer leverage were negatively related to cash payment method deals. This empirical study provided some new insights into the determinants of payment methods in Indian M&A deals. This study will help the decision-makers of both acquirers and targets to finalize the payment method of M&As in different corporate situations and facilitate the companies in improving their strategies for bringing in more synergy in the deals.